Environmental Legal Protection of Rivers in the Perspective of Sustainable Development - Trias Hernanda; Urip Giyono (Muhammadiyah University Press, 2021)
Objective: This research discusses the legal protection of the river environment from the perspective of sustainable development. The concept of sustainable development is especially important in guarding river protection, so it must really be applied. Methodology: The research method used in this study is normative juridical law research, namely examining legal rules and legal principles. Finding: Based on the study obtained, that river protection in Indonesia is still weak, as evidenced by the presence of garbage and waste found in several major rivers in Indonesia, in addition to the absence of concrete actions from the government in protecting rivers. Utility: This research is useful for evaluating protection measures and providing a reference for sanctions for river protection by the concept of sustainable development. Novelty/Originality: This study provides the idea that river protection can be optimized to reduce the level of pollution and river damage by properly applying the concept of sustainable development by the Environmental Protection and Management Act (UUPPLH) principle